Child behaviour checklist emotional dysregulation profiles in youth with disruptive behaviour disorders: Clinical correlates and treatment implications. Issue 1 (30th January 2015) - Masi, Gabriele; Muratori, Pietro; Manfredi, Azzurra; Pisano, Simone; Milone, Annarita
Abstract: Two Child Behaviour Checklist (CBCL) profiles were correlated to poor self-regulation, Deficient Emotional Self-Regulation (DESR) (elevation between 1 and 2 Standard Deviations (SD) in Anxiety/Depression, Aggression, Attention subscales), and Dysregulation Profile (DP) (elevation of 2 Standard Deviations or more). We explored youths with Oppositional Defiant Disorder (ODD) and Conduct Disorder (CD) whether these profiles are associated with specific clinical features. The sample included 57 patients with DESR profile and 41 with DP profile, ages 9 to 15 years, all assigned to a non-pharmacological Multimodal Treatment Program. No differences resulted between groups in demographic features, diagnosis ratio, and comorbidities with Attention Deficit Hyperactivity Disorder (ADHD), Bipolar Disorder (BD), and Anxiety Disorder. The DP group was associated with higher scores in Withdrawn, Social Problem, Thought, Rule Breaking, and Somatic CBCL subscales, and higher scores in Narcissism and Impulsivity (but not Callous–Unemotional (CU)), according to the Antisocial Process Screening Device (APSD). After treatment, patients with DESR improved their personality traits (Narcissistic and Callous–Unemotional, but not Impulsivity), while changes in CBCL scales were modest. Patients with DP improved scales of Attention, Aggression, Anxiety–Depression, Rule Breaking, Withdrawal, Social Problem and Thought, while personality features did not change. These results suggest diagnostic implications of CBCL profiles, and indications for targeted treatment strategies.